FDI contracts should include investor obligations on sustainable development - Sondra Faccio (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2024)
FDI contracts, especially in the extractive industry, increasingly feature investor obligations on sustainable development, with the aim of maximizing the contribution of FDI to sustainable development and attenuate its negative impacts. This Perspective illustrates some investor obligations on sustainable development contained in FDI contracts, discussing what are their benefits and how to make them more effective.
Keywords: 330